The SemSPM approach: fine integration of WS-SecurityPolicy semantics to enhance matching security policies in SOA. Issue 3 (September 2016) - Ben Brahim, Monia; Chaari, Tarak; Ben Jemaa, Maher; Jmaiel, Mohamed
Abstract The lack of semantics in WS-SecurityPolicy standard hampers the effectiveness of matching security policies. To resolve this problem, we present a semantic approach for matching Web service security policies. The approach consists in the transformation of WS-SP into an OWL-DL ontology and the definition of a set of rules which automatically generate semantic relations that can exist between the provider and requestor security requirements. We show how these relations lead to more correct and refined matching of security policies. We also describe the implementation details of our approach and its validation through a real-world use case.